Amoco CD commercial polypropylene catalyst tailor-made for the Amoco-Chisso gas phase process - Gregory Arzoumanidis (Polyolefins Journal, 2014)
The commercial profile of the Amoco CD MgCl2 supported polypropylene catalyst is presented. The development, the unique method of preparation/production, with emphasis on particle morphology, and the parameters affecting particle size (PS), particle size distribution (PSD), and particle shape are discussed in detail. The outstanding performance of the catalyst, tailoredmade for the Amoco-Chisso gas phase process, is attributable to synergistic effects, originating from catalyst and process design factors. Catalyst median particle size (d50) may be controlled in the 7-100 microns range. Parameters affecting PS and PSD during catalyst support preparation include: agitation speed, temperature, organic reagent to Mg ratios, morphology controlling agents, and deliberate spiking of the aromatic solvent used with appropriate contaminants. Particle shape variation between the cubic and spheroidal is affected by the types of reagents used, the ratios of these reagents to Mg, the time/temperature profile of the procedure, and the sequence of reagent addition during catalyst support preparation. Catalyst activation takes place in several steps by thermal treatment of the support with TiCl4/toluene solutions. Cost-effective TiCl4/toluene reuse system from theactivation streams has been put in place to reduce waste material considerably. There is an optimum temperature of activation close to 120˚C. The progress of activation as well as catalyst quality may be monitored by IR spectroscopy, expressed in easily identifiable IR fingerprint patterns, which correlate well with the catalyst performance. More recently a new concept of supported catalysts based on the CD technology has been developed. It features organometallic complexes instead of just TiCl4 as the polymerization active centers. The new catalysts show improved performance and advantageous polymer product properties. We suggest that the newly invented organometallic complexes may open a new era in polyolefin catalysis, including polyethylene copolymers. The success of the CD and Amoco-Chisso process is illustrated by the two dozen commercial plants worldwide that use the technology, and the recent licensing advances by Ineos, the successor of Amoco, for this polypropylene technology.